Legal Knowledge and Economic Development: The Case of Land Rights in Uganda - Deininger, Klaus; Ali, Daniel Ayalew; Yamano, Takashi (2012)
Although many African countries have recently embarked on revisions of their land legislations to give recognition to customary arrangements and strengthen women's rights, few studies assess the actual or potential economic impact of such steps. We use data from Uganda to assess the impact of tenure regime, perceived transfer rights, and legal knowledge on investment, productivity, and land values. While results support strong and positive investment-impacts of tenure and transferability, knowledge of the new law's provisions adds considerably to these, pointing towards substantial potential from disseminating the law that has not yet been fully realized.